Fredholm one-dimensional boundary-value problems with parameter in Sobolev spaces - Atlasiuk, O. M.; Mikhailets, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
For systems of linear differential equations on a compact interval, we investigate the dependence on a parameter ε of the solutions to boundary-value problems in the Sobolev spaces W^n_∞. We obtain a constructive criterion of the continuous dependence of the solutions of these problems on the parameter ε for ε = 0. The degree of convergence of these solutions is established.